PERAN ENVIRONMENTAL PERFORMANCE TERHADAP KINERJA PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL MEDIASI - Aisha Hanif; Hadiah Fitriyah; Rizky Eka Febriansah (Universitas Pakuan, 2020)
This study aims to determine the role of environmental performance on company performance with corporate social responsibility as a mediating variable. This research was conducted on all manufacturing companies that participated in the company performance rating (PROPER) program and companies listed on the Indonesia Stock Exchange during the period 2016-2018. The research method used is to use PLS (Partial Least Squares), namely SEM (Structural Equation Method) based on variance. The results of this study indicate that environmental performance has no effect on financial performance, environmental performance has an effect on corporate social responsibility, corporate social responsibility has no effect on financial performance, corporate social responsibility is unable to mediate the effect of environmental performance on corporate financial performance. The results of this study have implications for the company, namely as an evaluation material for companies in order to increase the quantity and quality of environmental management and their social responsibility activities so as to obtain positive feedback from the community and ultimately improve company performance which is proxied by increased corporate profits.